Reduced expression of PD-L1 in autoimmune thyroiditis attenuate trophoblast invasion through ERK/MMP pathway - Mengya Chen; Nduwimana Gilbert; Haixia Liu (BMC, 2019)
Abstract Background Autoimmune thyroiditis (AIT) with euthyroid is associated with miscarriage. But the exact mechanism remains unclear. Studies have shown that the programmed cell death-1 (PD-1)/programmed cell death -ligand 1 (PD-L1) pathway is essential for normal pregnancy. However, the expression of PD-L1 in gestational trophoblasts in mice with autoimmune thyroiditis and the mechanisms leading to miscarriage have not been fully investigated. Methods Immunofluorescence and Western blot were used to detect the expression of PD-L1, p-ERK, MMP-2 and MMP-9 in embryonic trophoblast cells of pregnant mice with AIT. The expression of PD-L1 in HTR-8/SVneo cells were silenced, and the expression of PD-L1, MMP-2, MMP-9, ERK and p-ERK1/2 was detected by Western blot analyses and immunofluorescence assays. Invasive assays were performed in PD-L1 silenced HTR-8/SVneo cells using a Transwell chamber. Results Compared with normal pregnancy, the expression of PD-L1, ERK, p-ERK, MMP-2 and MMP-9 in embryonic trophoblast cells was significantly lower in pregnant mice with AIT. Compared with the negative control (NC) group (cells transfected with negative control siRNA), phosphorylation of MMP-2, MMP-9 and P-ERK1/2 proteins was significantly reduced in HTR-8/SVneo cells transfected with PD-L1 siRNA, and the number of cells penetrating the membrane was reduced. Conclusion AIT inhibits ERK/MMP-2 and MMP-9 pathways through PD-L1 reduction, attenuates embryonic trophoblast invasion and ultimalely induces miscarriage ultimately.